Meningkatkan Nasionalisme dalam Karakter Pendidikan Kepramukaan - Ramadhani, Nurlaila; Dewi, Anggraeni; Furnamasari, Yayang Furi (Edumaspul: Jurnal Pendidikan, 2022)
The Indonesian Scout Movement is the name of a non-formal education organization that organizes scouting education carried out in Indonesia.  The purpose of this study was to determine the scout movement as an effort to increase nationalism in SDN 02 for the academic year 2020-2021.  In some character education programs can improve student citizenship attitudes and instill an attitude of nationalism.  Character education must instill the spirit of nationalism, love for the homeland, care for the environment around it.  Scouts teach Dasa Darma which shows the cultivation of character values ​​such as creativity, hard work, mutual help, independence, democracy, and responsibility.  Research uses qualitative in some cases such as through the collection of questionnaires and observations.